Agricultural Land Lease Analysis as a Phenomenon Continuously Connected to the Social and Economic Realities of the Romanian Society - Emil MUSAT; Rares-Alexandru IONESCU (Communications of International Proceedings, 2020)
The paper analyses the way and the rhythm in which the land lease regulation has evolved, in Romania, as a legal and economic operation necessary for the reintegration in the production process of agricultural land that was returned to former owners since 1991, in order to reduce the fragmentation of agricultural land and to increase size agricultural holdings, and to streamline the agricultural activity after strengthening the segment of agricultural professionals. The land lease legsilation was adopted in Romania in response to the need to organize the agricultural activity and the land market in the context of the agrarian reform started in 1991. By researching of the initiatives to amend the law, of the reasons invoked and of the parliamentary debates, are  highlighted, at some point, the needs of the business environment represented by the land lessee, of the landowners as lessors, as well as how the legislature manages to respond to them and to keep the land lease continuously connected to the realities of the Romanian society. The social interests of each moment are also reflected. This analysis is a useful tool for an in-depth understanding of the land lease operation and for understanding how this economic phenomenon impacts the society as a whole. This paper represents an approach supporting the idea that the land lease must benefit from a special regulatory law.
Keywords: Lease; history; law amendment.